"Cruel to be kind?" – is it beneficial for failing MRCPCH clinical examination candidates to be forced to delay their re-sit?. (24th May 2012) - Lee, LJ; Newell, SJ; Foard, LE; Muir, G; Simpson, MM; Windebank, KP
Abstract : Aims: Candidates achieving low scores in the MRCPCH Clinical are deferred from re-sitting for a specified period and advised to seek further training and educational support. The exam is scored out of 120, with a pass mark of 100. Candidates scoring 71 to 80 are deferred from sitting the next exam; those scoring ≤70, from sitting the next two exams. To explore whether deferment has any positive effect, candidates' past exam scores from first attempt to re-sit were analysed. Methods: Candidate performance was analysed over the period since 2004 when deferment was instituted (21 exam diets, UK and Overseas). 2156 candidates who had failed at their first attempt were identified. These were divided into those deferred for two diets (n=245), one diet (n=557) and those who had received no deferment (n=1354). Results: The mean change in marks from first attempt to re-sit (table 1 ) was compared for deferred and non-deferred candidate groups. A significant difference (t (56)=2.721, p<0.01) was found for candidates sitting the exam in Overseas centres. Further analysis of candidate re-sit performance suggests that deferment is effective in excluding candidates who are unlikely to pass in the following exam diet. Based on the distribution of re-sit scores of candidates scoring 82 or 84 it is estimated that fewer than 14% of those deferred for one diet would achieve the increase in marks required to pass in the next exam. Conclusion: The existing deferment process effectively safeguards Clinical exam places for those candidates with the best chance of passing and potentially protects the children used in the exam from inappropriate physical examination. The effects of deferment on re-sit performance vary according to exam location, and may depend on the quality of educational supervision and support, and the availability of preparatory courses.